Invasive pericardial hydatid cyst: Excision of multiple huge cysts - Kothari, Jignesh (J Saudi Heart Assoc, 2017)
Cardiac hydatid cyst is rare even in endemic countries, and poses a therapeutic challenge due to varying presentation and unpredictable pre-, peri-, and postoperative complications. We herein present a case of multiple, multifocal, huge pericardial hydatid cyst, with invasion into the left ventricle and main pulmonary artery in a young male patient, presented with atypical chest pain.